Impact of Social Support on Wellbeing and Health-Related Quality of Life among Elderly Women: Mediating Role of Physical Activity - Kamelia Abdi; Fatemeh Beigom Hosseini; Zahra Chaharbaghi; Saeed Ghorbani (Women’s Health Bulletin, 2022)
Background: Living with a better quality is considered as the main challenge for the elderly in new century. Therefore, examining the wellbeing and quality of life of the elderly has become a necessity. The purpose of this study was to test a conceptual model that examines the associations between social support with wellbeing and health-related quality of life in elderly women while considering physical activity as a mediator. Methods: The present study used a structural equation modelling approach. Participants were 384 elderlies (mean age of 62.22±10.55 years) from Golestan province, Iran in 2020. They were over 60 years old without any physical or mental disabilities. The participants fulfilled standard questionnaires (Perceived Social Support Scale, Rapid Assessment of Physical Activity, and Adult Well-Being Assessment). Spearman correlation test and structural equation modelling using Lisrel were employed to analyze data. Results: Findings showed that perceived social support directly affected physical activity (β=0.409, T=6.631), wellbeing (β=0.429, T=7.701), and health-related quality of life (β=0.473, T=7.927). Moreover, physical activity directly affected wellbeing (β=0.231, T=3.217) and health-related quality of life (β=0.627, T=10.649). Finally, physical activity acted as a significant mediator in the associations between perceived social support with wellbeing (Z=5.449, p <0.001) and health-related quality of life (Z=5.930, p <0.001). Conclusion: Social support and physical activity are critical concerns for elderly women. Appropriately, it is essential to embrace fitting procedures to increase social support and an active lifestyle among this population.